Особливості становлення мотиваційно-ціннісного комплексу музично обдарованої молоді - П'явка, Ігор (Східноєвропейський національний університет імені Лесі Українки, 2018)
The article is devoted to the study of the peculiarities of formation of the motivational-value complex of the musically gifted youth. The role of the motivational orientation of a personality as one of the peculiarities of value formation and development was established. Pedagogical musical psychology examines the psychological foundations of the musical training and education, the formation of a musician‟s personality. A personality‟s choice of personal and professional ways of life is largely determined by the process of formation of his or her value sphere. The orientation of the musically gifted personality, his or her actions, behavior and deeds depend on the system of values which are adopted and realized in life. The search for the gifted individuals in order to support their development is of great social significance. According to special studies, a very small percentage of people create those new cultural and technical values that form the basis of the well-being of all humanity or a certain nation. Who are these people? Creative and gifted personalities. It is very difficult to identify giftedness. First of all, it is hard to answer the question who should be considered gifted, especially if the search is conducted among children whose potential capabilities haven‟t been fully revealed yet. For the gifted youth it is important to make a valuable choice of future professional activity, which should inevitably become the meaning of life, which will be filled with joy, inspiration and which will dignify and enhance a personality. This is especially true in the choice of the musical profession, which should be raised in the consciousness of a future musician to the level of his or her meaning of life. Стаття присвячена вивченню особливостей становлення мотиваційно-ціннісного комплексу музично обдарованої молоді. З`ясована роль мотиваційної спрямованості особистості як однієї з особливостей становлення та розвитку цінностей. Choosing this path, in the process of self-determination a personality primarily becomes the carrier of a certain system of values, senses and type of consciousness.
Keywords: особистість; цінності; ціннісне становлення; музична обдарованість; професійна спрямованість; професійна мотивація